INDUKSI KALUS BAWANG MERAH (ALLIUM ASCALONICUM L.) LOKAL PALU PADA MEDIUM MS DENGAN PENAMBAHAN 2,4-D (2,4-ASAM DIKLOROPENOKSI ASETAT) DAN AIR KELAPA - Sorentina, Melisa S.M.; Haliani, Haliani; Muslimin, Muslimin; Suwastika, I Nengah (Natural Science: Journal of Science and Technology, 2013)
Shallot c.v. Local Palu (BML-Palu) is one of importance agricultural commodities in Palu and surrounding area of Central Sulawesi. Unfortunately, in agricultural system, it?s facing difficulties in seed propagation. However, tissue culture approach was a potential technology which can be applied in order to overtake the problem. Our study was an early step in the application of this technology. We tried to find out the best combination of 2,4-D and coconut water in MS based medium, which suitable for callus induction. This experimental study was based on Completely Randomized Design (CRD), with 4 treatments, 3 replications, and 3 shallot explants on each unit. The treatments were PK1 (MS0 + 1 ppm 2,4-D + 10% coconut water), PK2 (MS0 + 1,5 ppm 2,4-D + 10% coconut water), PK3 (MS0 + 2 ppm 2,4-D + 10% coconut water), and PK4 (MS0 + 2,5 ppm 2,4-D + 10% coconut water). Out came of this research showed that all treatments, except PK2, were able to induce callus formation up to 80.55% of total explants. Based on the observed parameters i.e. time of Callus emerging, frecuency of explants producing callus, callus morphology and callus cell observation; PK3 was the best medium in callus induction and growth. Callus on this medium was intermediate-type, white in color, active in  cell propagation, also uniform in size. While PK2 was fail to induce the callus due to overproduction of secondary metabolite.